De‐motivators for the adoption of agile methodologies for large‐scale software development teams: An SLR from management perspective. Issue 12 (24th June 2020) - Faisal Abrar, Muhammad; Sohail, M.; Ali, Sikandar; Faran Majeed, Muhammad; Ali Shah, Ibrar; Rashid, Nasir; Ullah, Naimat
Abstract: Most of the software development projects have traditionally been faced with severe problems in terms of quality, cost, and time. Researchers and practitioners have focused on agile software development methods (ASDMs) as an alternative to overcome these problems. Agile methods employ iterative development cycles, interspersed by user feedback. Agile methods were basically developed for small development teams. Scaling agile methods is a big issue from different perspectives. De‐motivators play a key role in project management as it allows early identification and prompt management of threats that may arise during project execution. The objective of this paper is to identify the de‐motivators while scaling agile at large, from management perspectives. We have adapted SLR and applied contrived search criteria derived from the research questions, followed by selecting the required research papers, data extraction, and data synthesis, which resulted in 15 de‐motivators from 58 relevant papers. Some of the identified de‐motivators are 'traditional organizational culture', 'lack of agile experts', 'reluctance to adopt', and 'lack of management and commitment support'. The identified factors have been compared from various perspectives, such as continents, digital libraries, organization size, and so forth.